Comorbidity of Depression with Physical Disorders: Research and Clinical Implications - Kang, Hee-Ju; Kim, Seon-Young; Bae, Kyung-Yeol; Kim, Sung-Wan; Shin, Il-Seon; Yoon, Jin-Sang; Kim, Jae-Min (Chonnam medical journal, 2015)
Depression is prevalent in patients with physical disorders, particularly in those with severe disorders such as cancer, stroke, and acute coronary syndrome. Depression has an adverse impact on the courses of these diseases that includes poor quality of life, more functional impairments, and a higher mortality rate. Patients with physical disorders are at higher risk of depression. This is particularly true for patients with genetic and epigenetic predictors, environmental vulnerabilities such as past depression, higher disability, and stressful life events. Such patients should be monitored closely. To appropriately manage depression in these patients, comprehensive and integrative care that includes antidepressant treatment (with considerations for adverse effects and drug interactions), treatment of the physical disorder, and collaborative care that consists of disease education, cognitive reframing, and modification of coping style should be provided. The objective of the present review was to present and summarize the prevalence, risk factors, clinical correlates, current pathophysiological aspects including genetics, and treatments for depression comorbid with physical disorders. In particular, we tried to focus on severe physical disorders with high mortality rates, such as cancer, stroke, and acute coronary syndrome, which are highly comorbid with depression. This review will enhance our current understanding of the association between depression and serious medical conditions, which will allow clinicians to develop more advanced and personalized treatment options for these patients in routine clinical practice.